MYELODYSPLASTIC SYNDROMES AND IRON CHELATION THERAPY - Emanuele Angelucci; Silvana Anna Maria Urru; Federica Pilo; Alberto Piperno (Mediterranean Journal of Hematology and Infectious Diseases)
Over recent decades we have been fortunate to witness the advent of new technologies and of an expanded knowledge and application of chelation therapies to the benefit of patients with iron overload. However, extrapolation of learnings from thalassemia to the myelodysplastic syndromes (MDS) has resulted in a fragmented and uncoordinated clinical evidence base. We’re therefore forced to change our understanding of MDS, looking with other eyes to observational studies that inform us about the relationship between iron and tissue damage in these subjects. The available evidence suggests that iron accumulation is prognostically significant in MDS, but levels of accumulation historically associated with organ damage (based on data generated in the thalassemias) are infrequent. Emerging experimental data have provided some insight into this paradox, as our understanding of iron-induced tissue damage has evolved from a process of progressive bulking of organs through high-volumes iron deposition, to one of ‘toxic’ damage inflicted through multiple cellular pathways. Damage from iron may therefore occur prior to reaching reference thresholds, and similarly, chelation may be of benefit before overt iron overload is seen. In this review, we revisit the science and clinical evidence for iron overload in MDS to better characterise the iron overload phenotype in these patients, which is distinct from the classical transfusional and non-transfusional iron overload syndrome. We hope this will provide a conceptual framework to better understand the complex associations between anemia, iron and clinical outcomes, to accelerate progress in this area.